Beijing Declaration and the Platform for Action (UN New YorkUS, 1996)
Presents a powerful agenda for the empowerment of women. Calls for the integration of gender perspectives in all policies and programmes. Focuses on concrete measures to address the critical areas of concern worldwide.
Additional copy located in the Office of the Secretary-General